High-strength, ultra-thin biodegradable film and method for producing same
By developing high-strength, ultra-thin branched aromatic copolyester biodegradable films, the problem of difficult degradation of traditional polyethylene cover films is solved, and the high mechanical properties and complete biodegradation of the material are achieved, and it is suitable for agricultural cover films and packaging materials.
Patent Information
- Application Number
- JP2022515876
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-17
- Filing Date
- 2020-09-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-09-17
AI Technical Summary
The traditional agricultural covering film materials are mainly polyethylene that is difficult to degrade, resulting in the increase in waste covering films in agricultural soils year by year, resulting in problems such as soil environmental deterioration, reduced soil moisture, soil hardening, reduced fertility and intensified pollution.
A high-strength, ultra-thin biodegradable membrane was developed, using branched aromatic copolyester as the main material, and the mechanical and degradable properties of the material were enhanced by blending with organic peroxides.
The biodegradable membrane is achieved in complete degradation under natural or compost conditions, has the same mechanical properties as low-density polyethylene films, and has good water and heat protection properties, which can completely replace traditional polyethylene covering films and packaging films.
Smart Images

Figure 0007658954000001 
Figure 0007658954000002 
Figure 0007658954000003
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field] The present invention relates to the field of biodegradable films, and in particular to a high strength, ultra-thin biodegradable film and a method for producing the same, as well as a copolyester for producing the biodegradable film.
[0002] [Background technology] At the end of the 1970s, mulching film cover cultivation technology was introduced in China. This technology has greatly improved crop yields in China, bringing remarkable economic benefits, and has been praised by people as a "white revolution" in agriculture. Since the first planting, mulching film technology has been widespread in more than 20 agricultural crops, including cotton, corn, beet, sugarcane, tomato, sweet potato, melon, etc. However, the widespread use of mulching film brings new problems. At present, traditional agricultural mulching film materials are mainly polyethylene (PE), but polyethylene is difficult to decompose under natural environmental conditions and lacks effective disposal methods. As a result, waste mulching film in agricultural soil is increasing year by year, and pollution is continuously becoming more serious. According to statistics, 200 tons to 300,000 tons of non-degradable residual mulching film are newly added to China's farmland every year. As a result, the soil environment is deteriorated, the soil moisture content is reduced, the soil is hardened, the fertility is reduced, and ultimately the yield of agricultural crops is reduced. Moreover, the mulching film fragments that are broken down and accumulated in the soil for a long time are completely uncontrollable and will eventually seep into the groundwater system or become suspended in the dust of the atmosphere, resulting in persistent and destructive disasters for people. Therefore, there is an urgent need to develop alternative, completely biodegradable mulching film materials.
[0003] The biodegradable mulching film material currently being developed and used is a polyester material containing an aliphatic-aromatic copolymer as the main film-forming material. The material has the most similar performance to polyethylene mulching film, for example, Ecoflex® developed by BASF, which is poly(terephthalic acid-adipic acid-butanediol) ester (PBAT). It has been demonstrated in detail in the literature (Chemosphere, 44 (2001), 289-299) that Ecoflex® can generate small molecule products, carbon dioxide and water. After being decomposed by bacteria widely present in soil, carbon dioxide and water are completely harmless to soil and air. However, the film products Ecoflex® and Ecovoi® (a mixture of Ecoflex® and PLA), as well as the PBAT products offered by some domestic manufacturers, all have shortcomings such as easy and early film breakage, insufficient mechanical properties, and inappropriate decomposition period when actually used as mulching films, and therefore cannot be fully deployed in the market as mulching film products.
[0004] [Contents of the invention] In order to solve the above problems of the prior art, the object of the present invention is to provide a high-strength, extremely thin, biodegradable film and its manufacturing method. The film product has excellent mechanical properties, as well as aging performance in line with the service cycle and excellent heat and water retention performance. As a result, it can be perfectly used as a biodegradable mulching film product, which is widely used in various regions, and can also be used as a biodegradable packaging material.
[0005] The first aspect of the present invention is a biodegradable film manufactured from a composition comprising a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d, and a copolyester obtained by extrusion reaction with an organic peroxide, wherein the monomer a is an aromatic dibasic acid or an ester derivative thereof; the monomer b is a C2-C 10 Aliphatic dihydric alcohols or C3-C 10 and the monomer c is one or more of the alicyclic dihydric alcohols of C4-C 20 or an ester derivative thereof; and said monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, an anhydride having a functionality greater than 2, an epoxy compound or an anhydride having a hydroxyl or carboxyl group, a glycidyl ester, a glycidyl ether, glycidol, a lactone having a side hydroxyl or carboxyl group, or a cyclic carbonate.
[0006] A second feature of the present invention is to provide a method for producing the biodegradable film, the method comprising the steps of: Step 1) A step of preparing a copolyester by extrusion reaction of a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d with an organic peroxide; the monomer a is an aromatic dibasic acid or its ester derivative; the monomer b is a C2-C 10 Aliphatic dihydric alcohols or C3-C 10 and the monomer c is one or more of the alicyclic dihydric alcohols of C4-C 20or an ester derivative thereof; and said monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, an anhydride having a functionality greater than 2, an epoxy compound or anhydride having hydroxyl or carboxyl groups, a glycidyl ester, a glycidyl ether, glycidol, a lactone having side hydroxyl or carboxyl groups, or a cyclic carbonate; step 2) extruding and granulating the copolyester obtained in step 1) to obtain a composition; and Step 3) blowing air through the composition to obtain the biodegradable film.
[0007] The third feature of the present invention is a copolyester obtained by extrusion reaction of a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d with an organic peroxide, wherein the monomer a is an aromatic dibasic acid or its ester derivative; the monomer b is a C2-C 10 Aliphatic dihydric alcohols or C3-C 10 and the monomer c is one or more of the alicyclic dihydric alcohols of C4-C 20 or an ester derivative thereof; and said monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, an anhydride having a functionality greater than 2, an epoxy compound or anhydride having hydroxyl or carboxyl groups, a glycidyl ester, a glycidyl ether, glycidol, a lactone having side hydroxyl or carboxyl groups, or a cyclic carbonate.
[0008] The film of the present invention is a high-strength film product produced by subjecting the main material, a branched, particularly long-branched, aliphatic-aromatic copolyester, to extrusion for chain extension and tackification, further increasing the length of the branched chains, the number of the branched chains and the entanglement degree of the branched chains, and, together with the use of corresponding processing aids, increasing the melt strength while decreasing the melt index. The film can be completely decomposed into small molecule products such as carbon dioxide and water under natural or composting conditions. Furthermore, the film can be produced to have a thickness of 4-50 μm as required, and its mechanical properties can reach the same level as those of LDPE polyethylene films with the same thickness. Furthermore, due to the mutual entanglement of the long branches, the film also has excellent water impermeability, and is expected to completely replace polyethylene in the field of mulching films and packaging films.
[0009] Further features and advantages of the present invention are described in the detailed description that follows.
[0010] Below is a detailed description of specific embodiments of the present invention. It is to be understood that the specific embodiments described herein are intended only to illustrate and explain the present invention and are not intended to be limiting.
[0011] According to a first embodiment of the present invention, the present invention provides a biodegradable film manufactured from a composition comprising a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d, and a copolyester obtained by extrusion reaction with an organic peroxide, wherein the monomer a is an aromatic dibasic acid or its ester derivative; the monomer b is a C2-C 10 Aliphatic dihydric alcohols or C3-C 10 and the monomer c is one or more of the alicyclic dihydric alcohols of C4-C 20or an ester derivative thereof; and said monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, an anhydride having a functionality greater than 2, an epoxy compound or an anhydride having a hydroxyl or carboxyl group, a glycidyl ester, a glycidyl ether, glycidol, a lactone having a side hydroxyl or carboxyl group, or a cyclic carbonate.
[0012] In the present invention, the branched aliphatic-aromatic copolyester is obtained by reacting monomer a, monomer b, monomer c, and monomer d under the action of a catalytic system containing a second catalyst. The second catalyst is represented by RE(R 3 ) 3, where RE is a rare earth metal element, and R 3 is a halogen, an alkoxy group, an aryloxy group, an acetylacetone group, and R 4 at least one selected from the group consisting of COO- groups, 4 is C1-C 30 Preferably, RE is lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium or scandium; the halogen is chlorine or bromine, the alkoxy group is a C3-C6 alkoxy group, the aryloxy group is an aryloxy group containing at least one benzene and / or naphthalene ring, and R 4 is C1-C 20 More preferably, RE is selected from lanthanum, cerium, praseodymium, neodymium or scandium, the halogen is chlorine or bromine, the alkyl group in the alkoxy group is isopropyl, n-butyl or isopentyl, the aryl group in the aryloxy group is 2,6-di-tert-butyl-4-methylphenyl or 4-butylphenyl, and R 4 is C3-C 18More preferably, the second catalyst is one or more selected from the group consisting of lanthanum acetylacetonate, neodymium acetylacetonate, neodymium isopropoxide, lanthanum isopropoxide, scandium isopropoxide, lanthanum stearate, neodymium stearate, lanthanum chloride, tris(2,6-di-tert-butyl-4-methylphenoxy)lanthanum, and hydrates thereof.
[0013] In the present invention, the catalyst system further comprises a first catalyst and / or a third catalyst.
[0014] The first catalyst is an oxide of M, M(OR 1 ) n and M(OOCR 2 ) m M is titanium, antimony or zinc; n and m are each independently a valence of M; R 1 is C1-C 10 and R 2 is C1-C 20 Preferably, the first catalyst is at least one selected from the group consisting of titanium alkoxide, antimony acetate, zinc acetate, zinc oxide, antimony oxide, and titanium oxide. More preferably, the first catalyst is at least one selected from the group consisting of tetrabutyl titanate (Ti(OC4H9)4), titanium isopropoxide, titanium dioxide, antimony trioxide, antimony acetate, and zinc acetate.
[0015] The third catalyst is at least one organotin compound. Preferably, the third catalyst is at least one selected from the group consisting of dibutyltin oxide, methylphenyltin oxide, tetraethyltin, hexaethyltin oxide, hexacyclohexylditin oxide, didodecyltin oxide, triethylhydroxytin, triphenylhydroxytin, triisobutyltin acetate, dibutyltin diacetate, diphenyltin dilaurate, monobutyltin trichloride, tributyltin chloride, dibutyltin sulfide, butylhydroxytin oxide, methyl stannic acid, ethyl stannic acid, and butyl stannic acid. More preferably, the third catalyst is a mixture of at least two selected from the group consisting of dibutyltin oxide, tetraethyltin, triphenylhydroxytin, dibutyltin diacetate, diphenyltin dilaurate, monobutyltin trichloride, tributyltin chloride, dibutyltin sulfide, butylhydroxytin oxide, methyl stannate, ethyl stannate, and butyl stannate. In this case, the amount of each component of the third catalyst may be 10 to 90 mol%, preferably 30 to 70 mol%.
[0016] The catalyst of the present invention may be used in an amount conventionally used in the art, and preferably, the total molar ratio of the catalyst to the monomer (a+c) is 1:1000-20000, and the molar ratio of the first catalyst to the second catalyst to the third catalyst is 0-20:0.1-10:0-1, preferably 0.1-20:0.1-10:1.
[0017] The monomer a may be selected from terephthalic acid, dimethyl terephthalate, phthalic acid, toluene dicarboxylic acid, naphthalenedicarboxylic acid, preferably terephthalic acid or dimethyl terephthalate; the monomer b may be selected from ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, preferably ethylene glycol, 1,3-propanediol or 1,4-butanediol; the monomer c may be selected from succinic acid, succinic anhydride, 1,5-glutaric acid, adipic acid, 1,10-sebacic acid or ester derivatives thereof, preferably succinic acid, succinic anhydride, dimethyl succinate, adipic acid or dimethyl adipate, particularly preferably 1, 4-succinic acid, succinic anhydride, dimethyl succinate, 1,6-adipic acid, or dimethyl 1,6-adipate; said monomer d may be selected from pyromellitic dianhydride, glycerol, pentaerythritol, glycidyl succinate, glycidyl adipate, glycidyl terephthalate, ethylene glycol glycidyl ether, 1,4-butanediol glycidyl ether, glycidic acid, glycidol, 3-hydroxyphthalic anhydride, 4-hydroxyphthalic anhydride, 3-hydroxymethylcaprolactone, 5- or 6-membered carbonates having alkylhydroxy or alkylcarboxyl groups, etc., preferably pyromellitic dianhydride, glycerol, or pentaerythritol.
[0018] Each monomer can be used in a conventional amount so long as a branched aliphatic-aromatic copolyester having a corresponding melt index is obtained, and preferably the amounts of monomer a, monomer b, monomer c, and monomer d are such that the molar ratio of (a+c) to b is 1:0.8-3, the molar ratio of (a+c) to d is 100-2000:1, and the molar ratio of a to c is 0:100-95:5, preferably 0:100-60:40.
[0019] The branched aliphatic-aromatic copolyesters are prepared by mixing monomer a, monomer b, monomer c and monomer d for esterification or transesterification reaction, or by mixing the esterification or transesterification product of monomer a and monomer b with the esterification or transesterification product of monomer c and monomer d for copolycondensation reaction under the action of a catalyst system.
[0020] The branched aliphatic-aromatic copolyester has a melt index of 2 to 100 g / 10 min, preferably 5 to 100 g / 10 min, under a load of 2.16 kg at 190° C. Preferably, the branched aliphatic-aromatic copolyester is long-chain.
[0021] According to the present invention, the organic peroxide is selected from organic peroxides having a half-life of 0.2 to 10 minutes, preferably 0.2 to 2 minutes, in the treatment temperature range.
[0022] More preferably, the organic peroxide is selected from a dialkyl peroxide, a diacyl peroxide, or a peroxy acid ester; the dialkyl peroxide is selected from dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, or di(tert-butylperoxyisopropyl)benzene; and the diacyl peroxide is selected from benzoyl peroxide or lauroyl peroxide.
[0023] In the present invention, the organic peroxide can be used in a conventional amount, for example, in an amount of 0.01 to 5 wt % based on the amount of the branched aliphatic-aromatic copolyester. Preferably, the organic peroxide is used in an amount of 0.01 to 1 wt % based on the amount of the branched aliphatic-aromatic copolyester.
[0024] Preferably, the copolyester has a melt index of 0.1 to 10 g / 10 min at 190° C. under a load of 2.16 kg.
[0025] According to the present invention, the composition also includes additives, such as antioxidants, slipping agents, anti-blocking agents, and nucleating agents. The additives may also include anti-UV agents, water-blocking agents, etc.
[0026] Based on 100 parts by weight of the copolyester, the amount of the antioxidant is 0.05 to 5 parts, the amount of the slip agent is 0.05 to 5 parts, the amount of the antiblocking agent is 0.05 to 5 parts, and the amount of the nucleating agent is 0.1 to 20 parts.
[0027] In order to obtain a film blowing material with better performance, preferably, based on 100 parts by weight of the copolyester, the amount of the antioxidant is 0.05-2 parts, the amount of the slip agent is 0.05-2 parts, the amount of the antiblocking agent is 0.05-2 parts, and the amount of the nucleating agent is 0.5-5 parts.
[0028] According to the present invention, any antioxidant conventionally used in the art can be used as the antioxidant.Preferably, said antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant in a mass ratio of 1:1; The hindered phenol antioxidant may be selected from Antioxidant 1010, Antioxidant 1076, Antioxidant 245, or Antioxidant 246; The phosphite antioxidant may be selected from triphenyl phosphate, trimethyl phosphate, or antioxidant 168.
[0029] In the present invention, the slip agent may be a stearate or an organic carboxylic acid amide; the stearate may preferably be calcium stearate, etc.; and the organic carboxylic acid amide may be erucamide or oleamide.
[0030] Preferably, the antiblocking agent is silica or talc.
[0031] Preferably, the nucleating agent is selected from hyperbranched polyamides, low density polyethylene or ethylene-methacrylic acid ionomers.
[0032] According to a second aspect, the present invention provides a method for producing said biodegradable film, namely a method comprising the steps of: Step 1) preparing a copolyester by extrusion reaction of a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d with an organic peroxide; The monomer a is an aromatic dibasic acid or an ester derivative thereof; the monomer b is a C2-C 10 Aliphatic dihydric alcohols or C3-C 10 and the monomer c is one or more of the alicyclic dihydric alcohols of C4-C 20 or an ester derivative thereof; and said monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, an anhydride having a functionality greater than 2, an epoxy compound or anhydride having hydroxyl or carboxyl groups, a glycidyl ester, a glycidyl ether, glycidol, a lactone having side hydroxyl or carboxyl groups, or a cyclic carbonate; Step 2) extruding and granulating the copolyester obtained in step 1) to obtain a composition; preferably, the composition is a film foaming material; and Step 3) A step of blowing air through the composition to obtain the biodegradable film.
[0033] In the present invention, the branched aliphatic-aromatic copolyester is obtained by reacting monomer a, monomer b, monomer c, and monomer d under the action of a catalytic system containing a second catalyst. The second catalyst is represented by RE(R3 ) 3, where RE is a rare earth metal element, and R 3 is a halogen, an alkoxy group, an aryloxy group, an acetylacetone group, and R 4 at least one selected from the group consisting of COO- groups, 4 is C1-C 30 Preferably, RE is lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium or scandium; the halogen is chlorine or bromine, the alkoxy group is a C3-C6 alkoxy group, the aryloxy group is an aryloxy group containing at least one benzene and / or naphthalene ring, and R 4 is C1-C 20 More preferably, RE is selected from lanthanum, cerium, praseodymium, neodymium or scandium, the halogen is chlorine or bromine, the alkyl group in the alkoxy group is isopropyl, n-butyl or isopentyl, the aryl group in the aryloxy group is 2,6-di-tert-butyl-4-methylphenyl or 4-butylphenyl, and R 4 is C3-C 18 More preferably, the second catalyst is one or more selected from the group consisting of lanthanum acetylacetonate, neodymium acetylacetonate, neodymium isopropoxide, lanthanum isopropoxide, scandium isopropoxide, lanthanum stearate, neodymium stearate, lanthanum chloride, tris(2,6-di-tert-butyl-4-methylphenoxy)lanthanum, and hydrates thereof.
[0034] In the present invention, the catalyst system further comprises a first catalyst and / or a third catalyst.
[0035] The first catalyst is an oxide of M, M(OR 1 ) n and M(OOCR 2 ) mM is titanium, antimony or zinc; n and m are each independently a valence of M; R 1 is C1-C 10 and R 2 is C1-C 20 Preferably, the first catalyst is at least one selected from the group consisting of titanium alkoxide, antimony acetate, zinc acetate, zinc oxide, antimony oxide, and titanium oxide. More preferably, the first catalyst is at least one selected from the group consisting of tetrabutyl titanate (Ti(OC4H9)4), titanium isopropoxide, titanium dioxide, antimony trioxide, antimony acetate, and zinc acetate.
[0036] The third catalyst is at least one organotin compound. Preferably, the third catalyst is at least one selected from the group consisting of dibutyltin oxide, methylphenyltin oxide, tetraethyltin, hexaethyltin oxide, hexacyclohexylditin oxide, didodecyltin oxide, triethylhydroxytin, triphenylhydroxytin, triisobutyltin acetate, dibutyltin diacetate, diphenyltin dilaurate, monobutyltin trichloride, tributyltin chloride, dibutyltin sulfide, butylhydroxytin oxide, methyl stannate, ethyl stannate, and butyl stannate. More preferably, the third catalyst is a mixture of at least two selected from the group consisting of dibutyltin oxide, tetraethyltin, triphenylhydroxytin, dibutyltin diacetate, diphenyltin dilaurate, monobutyltin trichloride, tributyltin chloride, dibutyltin sulfide, butylhydroxytin oxide, methyl stannate, ethyl stannate, and butyl stannate. In this case, the amount of each component of the third catalyst may be 10 to 90 mol%, preferably 30 to 70 mol%.
[0037] In the present invention, the total molar ratio of the catalyst to the monomer (a+c) is 1:1000-20000, and the molar ratios of the first catalyst, the second catalyst, and the third catalyst are 0-20:0.1-10:0-1, preferably 0.1-20:0.1-10:1.
[0038] The monomer a may be selected from terephthalic acid, dimethyl terephthalate, phthalic acid, toluene dicarboxylic acid, naphthalenedicarboxylic acid, preferably terephthalic acid or dimethyl terephthalate; the monomer b may be selected from ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, preferably 1,3-propanediol or 1,4-butanediol; the monomer c may be selected from succinic acid, succinic anhydride, 1,5-glutaric acid, adipic acid, 1,10-sebacic acid, or an ester derivative thereof, preferably succinic acid, succinic anhydride, dimethyl succinate, adipic acid or dimethyl adipate, particularly preferably 1,4-succinic acid. the monomer d may be selected from pyromellitic dianhydride, glycerol, pentaerythritol, glycidyl succinate, glycidyl adipate, glycidyl terephthalate, ethylene glycol glycidyl ether, 1,4-butanediol glycidyl ether, glycidic acid, glycidol, 3-hydroxyphthalic anhydride, 4-hydroxyphthalic anhydride, 3-hydroxymethylcaprolactone, 5-membered ring, 6-membered ring carbonate having an alkylhydroxy group or an alkylcarboxyl group, etc., preferably pyromellitic dianhydride, glycerol or pentaerythritol.
[0039] In order to obtain a branched aliphatic-aromatic copolyester with better performance, the amounts of monomer a, monomer b, monomer c, and monomer d are preferably such that the molar ratio of (a+c) to b is 1:0.8-3, the molar ratio of (a+c) to d is 100-2000:1, and the molar ratio of a to c is 0:100-95:5, preferably 0:100-60:40, and a+c represents the total amount of the monomer a and the monomer c.
[0040] In the present invention, the branched aliphatic-aromatic copolyester is prepared by mixing monomer a, monomer b, monomer c and monomer d for esterification or transesterification reaction, or by mixing the esterification or transesterification product of monomer a and monomer b with the esterification or transesterification product of monomer c and monomer d for copolycondensation reaction under the action of a catalyst system.
[0041] In the present invention, the conditions of the esterification or transesterification reaction and the polycondensation reaction can be conventionally selected according to the prior art. For example, the temperature of the esterification or transesterification reaction can be 150-230°C, preferably 150-220°C, and the reaction can be carried out for 2-4 hours under normal pressure or slight negative pressure; the polycondensation reaction conditions include a temperature of 230-270°C, preferably 235-260°C, more preferably 250-270°C, a pressure of 20-1000 Pa, and a time of 2-6 hours, preferably 2-3 hours.
[0042] The branched aliphatic-aromatic copolyester has a melt index of 2 to 100 g / 10 min, preferably 5 to 100 g / 10 min, at 190° C. under a load of 2.16 kg.
[0043] Preferably, the extrusion temperature in step 1) is 130-190°C from low to high in various zones of the extruder, preferably, the extrusion temperature is 150-180°C, more preferably, the extrusion temperature is 160-180°C.
[0044] Preferably, the copolyester obtained in step 1) has a melt index of 0.1 to 10 g / 10 min at 190° C. under a load of 2.16 kg.
[0045] In the present invention, the copolyester is also mixed with additives in step 2), the additives including antioxidants, slip agents, antiblocking agents, and nucleating agents. The additives can also include UV inhibitors, water blocking agents, etc.
[0046] In the present invention, the antioxidant, slip agent, antiblocking agent, and nucleating agent can be used in amounts conventionally used in the art. Based on 100 parts by weight of the copolyester, the amount of the antioxidant is 0.05 to 5 parts, the amount of the slip agent is 0.05 to 5 parts, the amount of the antiblocking agent is 0.05 to 5 parts, and the amount of the nucleating agent is 0.1 to 20 parts. Preferably, based on 100 parts by weight of the copolyester, the amount of the antioxidant is 0.05 to 2 parts, the amount of the slip agent is 0.05 to 2 parts, the amount of the antiblocking agent is 0.05 to 2 parts, and the amount of the nucleating agent is 0.5 to 5 parts.
[0047] According to the present invention, any antioxidant conventionally used in the art can be used as the antioxidant.Preferably, the antioxidant is a mixture of hindered phenol antioxidant and phosphite antioxidant in a mass ratio of 1:1; the hindered phenol antioxidant is selected from Antioxidant 1010, Antioxidant 1076, Antioxidant 245 or Antioxidant 246; the phosphite antioxidant can be selected from triphenyl phosphate, trimethyl phosphate or Antioxidant 168.
[0048] In the present invention, the slip agent may be a stearate or an organic carboxylic acid amide; the stearate may be calcium stearate, etc.; and the organic carboxylic acid amide may be erucamide or oleamide.
[0049] Preferably, the antiblocking agent is silica or talc.
[0050] Preferably, the nucleating agent is selected from hyperbranched polyamide, low density polyethylene or ethylene-methacrylic acid ionomer.
[0051] Preferably, in the step 2), the extrusion temperature is 130 to 190°C, preferably 150 to 190°C, and more preferably 160 to 180°C.
[0052] Preferably, in the step 3), the blow-up ratio is 3-8 and the film blowing temperature is 150-180°C.
[0053] Preferably, the present invention provides a method for producing said biodegradable film, namely a method comprising the following steps: Step 1) preparing a branched aliphatic-aromatic copolyester: mixing monomer a, monomer b, monomer c and monomer d for esterification or transesterification reaction, or mixing the esterification or transesterification product of monomer a and monomer b with the esterification or transesterification product of monomer c and monomer d for copolycondensation reaction under the action of a catalyst system; The monomer a is an aromatic dibasic acid or an ester derivative thereof; the monomer b is a C2-C 10 Aliphatic dihydric alcohols or C3-C 10 and the monomer c is one or more of the alicyclic dihydric alcohols of C4-C 20or an ester derivative thereof; and said monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, or an anhydride having a functionality greater than 2; Step 2) a step of carrying out an extrusion reaction of the branched aliphatic-aromatic copolyester produced in step 1) with an organic peroxide to produce a copolyester; Step 3) mixing the copolyester obtained in step 2) with an antioxidant, a slip agent, an antiblocking agent and a nucleating agent, and extruding and granulating the mixture to prepare a film foaming material; and Step 4) blow molding the film foam material to obtain the biodegradable film.
[0054] According to a third aspect of the present invention, there is provided a copolyester obtained by extrusion reaction of a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d with an organic peroxide, the copolyester comprising: The monomer a is an aromatic dibasic acid or an ester derivative thereof; The monomer b is C2-C 10 Aliphatic dihydric alcohols or C3-C 10 alicyclic dihydric alcohols; The monomer c is C4-C 20 or an ester derivative thereof; The monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, an anhydride having a functionality greater than 2, an epoxy compound or anhydride having a hydroxyl or carboxyl group, a glycidyl ester, a glycidyl ether, a glycidol, a lactone having a side hydroxyl or carboxyl group, or a cyclic carbonate, the characteristics of the copolyester being as described above in the first characteristic of the copolyester of the biodegradable film.
[0055] The biodegradable film of the present invention is a high strength, ultra-thin, biodegradable film having one or more of the following properties: a) thickness 4-50μm; b) Density 1.20~1.26g / cm 3 ; c) Haze 40%~90%; d) Surface haze 39%~89%; e) Internal haze 1%~50%; f) Light transmittance 80%~95%; g) Water permeability 100~3000g / m 2 / day; h) dart impact 20~600N; i) Yield point 4%~60%; j) Tensile load 1-50N; k) Tensile strength at yield 4~25MPa; l) Tensile strength at break: 6-200MPa; m) elongation at break 20% to 2000%; and n) Right angle tear load: 0.04~10N.
[0056] The parameters not defined in the present invention are all common technical means in the art.
[0057] The invention will be further described below with reference to examples, however the invention is not limited to these examples.
[0058] The data in the following examples and comparative examples are determined according to the following methods: The molecular weight and molecular weight distribution of the polymers were determined by gel permeation chromatography (GPC) using a Waters-208 instrument (with a Waters 2410 RI detector, flow rate 1.5 mL / min, 30 °C) with tetrahydrofuran (THF) as the solvent, and the molecular weights are calibrated with styrene standards.
[0059] The crystallization temperature (Tc), melting temperature (Tm) and glass transition temperature (Tg) of the polymers are determined by differential scanning calorimetry (DSC). Each sample is heated from -100°C to 250°C using a PerkinElmer Pyris 1 tester and subjected to two heating scans and one cooling scan at a ramping rate of 20°C / min, with Tm and Tg being obtained from the second heating scan and Tc being obtained from the cooling scan.
[0060] The melt index (MI) of a polymer is determined using an American Scientific Instruments CS-127 melt index tester at 190°C under a load of 2.16 kg according to the standard ISO 1133-2005 "Determination of melt mass-flow rate and melt volume-flow rate of thermoplastics".
[0061] The density is determined according to method GB / T4472-2011.
[0062] The light transmittance, total haze, and internal haze were all determined according to standard GB / T2410-2008 using a WGT-S type light transmittance / haze tester manufactured by Shanghai Shenguang Instrument Co. Ltd., with the surface haze being equal to the total haze minus the internal haze.
[0063] The water permeability is determined according to standard GB / T26253-2010 using a MOCON Permatran-W3 / 34 water vapor permeability tester.
[0064] The dart impact strength is determined according to standard ASTM D1709 using a Noselabats dart impact tester.
[0065] The yield point, tensile load, tensile strength at yield, tensile strength at break and elongation at break are determined according to standard GBT 13022-1991 using a Shimadzu AGS-X tensile tester.
[0066] The perpendicular tear load is determined using a Shimadzu AGS-X tensile tester according to standard QB / T1130-1991.
[0067] For the xenon lamp aging test, an X-65 type xenon lamp weathering box is used. The lamp source is 340 nm UV-A, the duration is 4 hours, and the intensity is 0.80 W / m 2 2 hours, dark dew, 45° C. The test is carried out according to standard GB / T16422.2-2014, and the total test time is 208 hours.
[0068] The sources of chemicals used in the following examples and comparative examples are given in Table a.
[0069] [Table 1]
[0070] *Lanthanum stearate is prepared according to Chinese Patent Application No. ZL 200510135517.2. Specifically, as described in Example A5, a calculated amount of Ln2O3 was weighed in a beaker, and an appropriate amount of distilled water was added, and then an excess amount of HCl was added and heated to dissolve the compound into a clear solution s3; an excess amount of stearic acid was weighed in another beaker, and an appropriate amount of absolute ethanol was added and heated to form a clear solution s4; the solutions s4 and s3 were added successively to a 100ml round-bottom flask, and then 10mg of phase transfer catalyst tetrabutylammonium bromide and a magnetic pole were added. A condenser was connected to the top of the flask, which was protected by nitrogen gas. The system was heated in an oil bath at a temperature below 100°C with magnetic stirring for about 5 hours. The flask was removed, and the reaction liquid was separated with a separatory funnel, after which the lower clear liquid was collected and evaporated to dryness.
[0071] Examples 1 to 8 are used to illustrate the biodegradable film of the present invention and its manufacturing method.
[0072] Example 1 A method for producing the biodegradable film, the method comprising the steps of: Step 1) Preparation of a branched aliphatic-aromatic copolyester: under the action of a catalyst, 423.8 g (2.55 mol) of monomer a terephthalic acid (PTA), 650 g (7.21 mol) of monomer b 1,4-butanediol (BDO), 330 g (2.79 mol) of monomer c succinic acid (SA) and 1 g (0.01 mol) of monomer d mixing glycerol and reacting in a reactor (esterification at 150-230°C and polycondensation at 230-260°C), the branched aliphatic-aromatic copolyester produced had a melt index of 23 g / 10 min at 190°C under a load of 2.16 kg, and the catalyst contained 0.245 g tetrabutyl titanate, 0.31 g lanthanum stearate, 0.1 g dibutyltin oxide and 0.14 g triphenylhydroxytin; step 2) subjecting 500 g of the branched aliphatic-aromatic copolyester produced in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in a German Kekuron zsk25 twin screw extruder, the various zones being at temperatures of 130-150-170°C to produce a copolyester, the copolyester having a melt index of 2.2 g / 10 min at 190°C under a load of 2.16 kg; step 3) 500g of the copolyester prepared in step 2) was mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a German Kekuron zsk25 twin screw extruder, the various zones were at a temperature of 130-150-170°C to obtain a film foaming material; Step 4) The film foaming material was blown in a German Collin ep30 film blowing machine at a film blowing temperature of 150-190°C and a blow-up ratio of 5-8 to obtain a film with a thickness of 10 μm.
[0073] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0074] Example 2 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing a branched aliphatic-aromatic copolyester: 423.8g (2.55mol) of monomer a terephthalic acid (PTA), 570.8g (7.5mol) of monomer b 1,3-propanediol, 438.4g (3mol) of monomer c dimethyl succinate, and 1g (0.0046mol) of monomer d pyromellitic dianhydride were mixed and reacted under the action of a catalyst, the branched aliphatic-aromatic copolyester having a melt index of 15g / 10min at 190°C under a load of 2.16kg, the catalyst comprising 0.245g tetrabutyl titanate, 0.31g lanthanum stearate, 0.1g dibutyltin oxide, and 0.14g triphenylhydroxytin; step 2) preparing a copolyester by subjecting 500 g of the branched aliphatic-aromatic copolyester prepared in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C., the prepared copolyester having a melt index of 1.8 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0075] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0076] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0077] Example 3 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing a branched aliphatic-aromatic copolyester: 679.6 g (3.5 mol) of monomer a dimethyl terephthalate, 570.8 g (7.5 mol) of monomer b 1,3-propanediol, 657.6 g (4.5 mol) of monomer c adipic acid, and 0.7 g (0.005 mol) of monomer d pentaerythritol were mixed and reacted under the action of a catalyst, the branched aliphatic-aromatic copolyester having a melt index of 40 g / 10 min at 190° C. under a load of 2.16 kg, the catalyst comprising 0.245 g tetrabutyl titanate, 0.31 g lanthanum stearate, 0.1 g dibutyltin oxide, and 0.14 g triphenylhydroxytin; step 2) preparing a copolyester by subjecting 500 g of the branched aliphatic-aromatic copolyester prepared in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C., the prepared copolyester having a melt index of 2.8 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0078] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0079] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0080] Example 4 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing a branched aliphatic-aromatic copolyester: 423.8g (2.55mol) of monomer a terephthalic acid (PTA), 650g (7.21mol) of monomer b 1,4-butanediol (BDO), 330g (2.79mol) of monomer c succinic acid (SA), and 1g (0.01mol) of monomer d glycerol were mixed and reacted under the action of a catalyst, the branched aliphatic-aromatic copolyester having a melt index of 40g / 10min at 190°C under a load of 2.16kg, the catalyst comprising 0.174g tetrabutyl titanate, 0.071g dibutyltin oxide, 0.099g triphenylhydroxytin, and 0.22g lanthanum stearate; step 2) preparing a copolyester by subjecting 500 g of the branched aliphatic-aromatic copolyester prepared in step 1) and 5 g of lauroyl peroxide to an extrusion reaction in an extruder at a temperature of 180° C., the prepared copolyester having a melt index of 2.6 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 180°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0081] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0082] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0083] Example 5 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing a branched aliphatic-aromatic copolyester: 423.8g (2.55mol) of monomer a terephthalic acid, 570.8g (7.5mol) of monomer b 1,3-propanediol, 438.4g (3mol) of monomer c dimethyl succinate, and 1g (0.0046mol) of monomer d pyromellitic dianhydride were mixed and reacted under the action of a catalyst, the branched aliphatic-aromatic copolyester having a melt index of 80g / 10min at 190°C under a load of 2.16kg, the catalyst comprising 0.245g tetrabutyl titanate, 0.31g lanthanum stearate, 0.1g dibutyltin oxide, and 0.14g triphenylhydroxytin; step 2) preparing a copolyester by subjecting 500 g of the branched aliphatic-aromatic copolyester prepared in step 1) and 0.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 160° C., the prepared copolyester having a melt index of 1.5 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 160°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0084] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0085] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0086] Example 6 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing a branched aliphatic-aromatic copolyester: 423.8 g (2.55 mol) of monomer a terephthalic acid (PTA), 650 g (7.21 mol) of monomer b 1,4-butanediol (BDO), 330 g (2.79 mol) of monomer c succinic acid (SA), and 1 g (0.01 mol) of monomer d glycerol were mixed and reacted under the action of a catalyst, the branched aliphatic-aromatic copolyester having a melt index of 25 g / 10 min at 190° C. under a load of 2.16 kg, the catalyst comprising 0.245 g tetrabutyl titanate, 0.31 g lanthanum stearate, 0.1 g dibutyltin oxide, and 0.14 g triphenylhydroxytin; step 2) preparing a copolyester by subjecting 500 g of the branched aliphatic-aromatic copolyester prepared in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C., the prepared copolyester having a melt index of 1.8 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1.5g of antioxidant 246, 1.5g of triphenyl phosphate, 1g of slip agent calcium stearate, 1g of antiblocking agent talc, and 5g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0087] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0088] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0089] Example 7 A method for producing the biodegradable film, the method comprising the steps of: Step 1) Preparation of a branched aliphatic-aromatic copolyester: Under the action of a catalyst, 423.8 g (2.55 mol) of monomer a terephthalic acid (PTA) and 650 g (7.21 mol) of monomer b 1,4-butanediol (BDO) are subjected to an esterification reaction to obtain 330 g (2.79 mol) of monomer c succinic acid (SA) and 1 g (0.01 mol) of monomer d subjecting glycerol to an esterification reaction, and then mixing the two esterification products to carry out a copolycondensation reaction, wherein the branched aliphatic-aromatic copolyester produced had a melt index of 42 g / 10 min at 190° C. under a load of 2.16 kg, and the catalyst contained 0.245 g of tetrabutyl titanate, 0.31 g of lanthanum stearate, 0.1 g of dibutyltin oxide, and 0.14 g of triphenylhydroxytin; step 2) preparing a copolyester by subjecting 500 g of the branched aliphatic-aromatic copolyester prepared in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C., the prepared copolyester having a melt index of 2.4 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0090] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0091] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0092] Example 8 Step 1) preparing a branched aliphatic-aromatic copolyester: 423.8g (2.55mol) of monomer a terephthalic acid (PTA) and 650g (7.21mol) of monomer b 1,4-butanediol (BDO) were subjected to esterification reaction under the action of a catalyst, and 330g (2.79mol) of monomer c succinic acid (SA) and 1g (0.01mol) of monomer d glycerol were subjected to esterification reaction, and then the two esterification products were mixed to carry out a copolycondensation reaction, wherein the prepared branched aliphatic-aromatic copolyester had a melt index of 80g / 10min at 190°C under a load of 2.16kg, and the catalyst was 0.62g of lanthanum stearate; step 2) preparing a copolyester by subjecting 500 g of the branched aliphatic-aromatic copolyester prepared in step 1) and 3.6 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C., the prepared copolyester having a melt index of 3.2 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0093] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0094] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0095] Comparative Example 1 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing a branched aliphatic-aromatic copolyester: 423.8g (2.55mol) of monomer a terephthalic acid (PTA), 650g (7.21mol) of monomer b 1,4-butanediol (BDO), 330g (2.79mol) of monomer c succinic acid (SA) and 1g (0.01mol) of monomer d glycerol were mixed and reacted under the action of a catalyst, the branched aliphatic-aromatic copolyester having a melt index of 20g / 10min at 190°C under a load of 2.16kg, the catalyst comprising 0.245g tetrabutyl titanate, 0.31g lanthanum stearate, 0.1g dibutyltin oxide and 0.14g triphenylhydroxytin; Step 2) mixing 500g of the branched aliphatic-aromatic copolyester prepared in step 1) with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjecting the mixture to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 3) The film foaming material was blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0096] For the conditions and apparatus for the above steps 1) to 3), see the corresponding steps in Example 1.
[0097] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0098] Comparative Example 2 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing an aliphatic-aromatic copolyester: mixing and reacting 423.8g (2.55mol) of monomer a terephthalic acid (PTA), 650g (7.21mol) of monomer b 1,4-butanediol (BDO) and 330g (2.79mol) of monomer c succinic acid (SA) under the action of a catalyst, the aliphatic-aromatic copolyester having a melt index of 30g / 10min at 190°C under a load of 2.16kg, the catalyst comprising 0.245g tetrabutyl titanate, 0.31g lanthanum stearate, 0.1g dibutyltin oxide and 0.14g triphenylhydroxytin; step 2) preparing a copolyester by subjecting 500 g of the aliphatic-aromatic copolyester prepared in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C., the prepared copolyester having a melt index of 5 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0099] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0100] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0101] Comparative Example 3 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing a branched aliphatic-aromatic copolyester: esterification of 423.8 g (2.55 mol) of monomer a terephthalic acid (PTA) and 650 g (7.21 mol) of monomer b 1,4-butanediol (BDO) under the action of a catalyst, followed by reaction of 330 g (2.79 mol) of monomer c succinic acid (SA) and 1 g (0.01 mol) of monomer d glycerol, the prepared branched aliphatic-aromatic copolyester having a melt index of 100 g / 10 min at 190° C. under a load of 2.16 kg, the catalyst being 0.45 g of tetrabutyl titanate; step 2) preparing a copolyester by subjecting 500 g of the aliphatic-aromatic copolyester prepared in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C., the prepared copolyester having a melt index of 5 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0102] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0103] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0104] Comparative Example 4 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing an aliphatic-aromatic copolyester: mixing and reacting 423.8g (2.55mol) of monomer a terephthalic acid (PTA), 650g (7.21mol) of monomer b 1,4-butanediol (BDO) and 330g (2.79mol) of monomer c succinic acid (SA) under the action of a catalyst, the aliphatic-aromatic copolyester having a melt index of 60g / 10min at 190°C under a load of 2.16kg, the catalyst being 0.62g of lanthanum stearate; step 2) preparing a copolyester by subjecting 500 g of the aliphatic-aromatic copolyester prepared in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C., the prepared copolyester having a melt index of 5 g / 10 min at 190° C. under a load of 2.16 kg; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0105] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0106] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0107] Comparative Example 5 A method for producing the biodegradable film, the method comprising the steps of: Step 1) preparing a branched aliphatic-aromatic copolyester: 423.8g (2.55mol) of monomer a terephthalic acid (PTA), 650g (7.21mol) of monomer b 1,4-butanediol (BDO), 330g (2.79mol) of monomer c succinic acid (SA) and 1g (0.01mol) of monomer d glycerol were mixed and reacted under the action of a catalyst, the branched aliphatic-aromatic copolyester having a melt index of 20g / 10min at 190°C under a load of 2.16kg, the catalyst comprising 0.245g tetrabutyl titanate, 0.1g dibutyltin oxide and 0.14g triphenylhydroxytin; step 2) preparing a copolyester by subjecting 500 g of the branched aliphatic-aromatic copolyester prepared in step 1) and 2.5 g of benzoyl peroxide to an extrusion reaction in an extruder at a temperature of 170° C.; Step 3) 500g of the copolyester prepared in step 2) is mixed with 1g of antioxidant 1010, 1g of antioxidant 168, 2.25g of slip agent erucamide, 2.25g of antiblocking agent silica, and 10g of nucleating agent Dupont Surlyn 8920 resin, and subjected to melt extrusion and granulation in a twin-screw extruder at a temperature of 170°C to obtain a film foaming material; Step 4) The film foaming material is blown by a film blowing machine to obtain a film having a thickness of 10 μm.
[0108] For the conditions and apparatus for the above steps 1) to 4), see the corresponding steps in Example 1.
[0109] The obtained film was subjected to performance tests, and the test results for optical properties, thermal properties, barrier properties, and aging properties are shown in Table 1, and the mechanical properties are shown in Table 2.
[0110] [Table 2]
[0111] [Table 3]
[0112] From the data in Tables 1 and 2, it can be seen that, compared to Comparative Example 1, which does not include a chain extension and tackification step, and Comparative Example 2, which includes an aliphatic-aromatic copolyester made with only three monomers, the films made in Examples 1 to 7 of the present invention all have better optical properties than the films of Comparative Examples 1 and 2, essentially the same thermal properties as the films of Comparative Examples 1 and 2, essentially better barrier and aging properties than the films of Comparative Examples 1 and 2, and generally better mechanical properties than the films of Comparative Examples 1 and 2. Furthermore, compared to Comparative Example 3, which includes an aliphatic-aromatic copolyester made with only the first catalyst, and Comparative Example 4, which includes an aliphatic-aromatic copolyester made with only three monomers, the film made in Example 8 of the present invention has better optical properties than the films of Comparative Examples 3 and 4, essentially the same thermal properties as the films of Comparative Examples 3 and 4, better barrier and aging properties than the films of Comparative Examples 3 and 4, and essentially better mechanical properties than the films of Comparative Examples 3 and 4. Moreover, compared to Comparative Example 5, which includes an aliphatic-aromatic copolyester made using only the first and third catalysts, the films made in Examples 1-8 of the present invention have better optical properties than the film of Comparative Example 5, essentially equivalent thermal properties to the film of Comparative Example 5, and better barrier properties, aging properties, and overall mechanical properties than the film of Comparative Example 5.
[0113] Although the embodiment of the present invention has been described above, the above description is illustrative and not exhaustive, and the present invention is not limited to the embodiment. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the embodiment.
Claims
1. A biodegradable film produced from a composition comprising a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d, and a copolyester obtained by extrusion reaction with an organic peroxide, The monomer a is an aromatic dibasic acid or an ester derivative thereof; The monomer b is C 2 -C 10 or an aliphatic dihydric alcohol of C 3 -C 10 and The monomer c is C 4 -C 20 or an ester derivative thereof; said monomer d being one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, an anhydride having a functionality greater than 2; The branched aliphatic-aromatic copolyester is obtained by reacting monomer a, monomer b, monomer c, and monomer d under the action of a catalytic system including at least the second catalyst among a first catalyst, a second catalyst, and a third catalyst; The second catalyst is 3 ) 3 is a compound in which RE is a rare earth metal element, R 3 is a halogen atom, an alkoxy group, an aryloxy group, an acetylacetone group, and R 4 At least one selected from the group consisting of COO- groups, R 4 is C 1 -C 30 is an alkyl group of the formula said first catalyst, when present, is one or more selected from the group consisting of an oxide of M, M(OR 1 ) n and M(OOCR 2 ) m , where M is titanium, antimony or zinc, n and m are each independently a valence of M, R 1 is a C 1 -C 10 alkyl group, and R 2 is a C 1 -C 20 alkyl group; and said third catalyst, when present, is at least one organotin compound; The composition also includes additives, the additives including antioxidants, slip agents, antiblocking agents, and nucleating agents.
2. RE (R 3 ) 3 In the compound of formula (I), RE is lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium, or scandium; The halogen is chlorine or bromine, and the alkoxy group is C 3 -C 6 The aryloxy group is an aryloxy group containing at least one benzene ring and / or naphthalene ring, R 4 is C 1 -C 20 The biodegradable film according to claim 1 , wherein the alkyl group is selected from the group consisting of:
3. The biodegradable film of claim 1 , wherein the catalyst system further comprises a first catalyst and / or a third catalyst.
4. the total molar ratio of the catalyst to the monomers (a+c) is 1:1000-20000; The biodegradable film according to claim 3, wherein the molar ratio of the first catalyst to the second catalyst to the third catalyst is 0-20:0.1-10:0-1, or 0.1-20:0.1-10:
1.
5. 5. A biodegradable film according to any one of claims 1 to 4, wherein the amounts of the various monomers are such that the molar ratio of (a+c) to b is 1:0.8-3, the molar ratio of (a+c) to d is 100-2000:1, and the molar ratio of a to c is 0:100-95:5, or 0:100-60:
40.
6. The monomer a is selected from terephthalic acid or dimethyl terephthalate; The monomer b is selected from ethylene glycol, 1,3-propanediol, or 1,4-butanediol; said monomer c is selected from succinic acid, succinic anhydride, dimethyl succinate, adipic acid or dimethyl adipate; The biodegradable film according to any one of claims 1 to 5, wherein the monomer d is selected from pyromellitic dianhydride, glycerol, pentaerythritol, glycidyl succinate, glycidyl adipate, glycidyl terephthalate, ethylene glycol glycidyl ether, 1,4-butanediol glycidyl ether, glycidic acid, glycidol, 3-hydroxyphthalic anhydride, 4-hydroxyphthalic anhydride, 3-hydroxymethylcaprolactone, and carbonates having a 5-membered or 6-membered ring and an alkylhydroxy group or an alkylcarboxyl group.
7. The branched aliphatic-aromatic copolyester comprises The biodegradable film according to any one of claims 1 to 6, which is produced such that, under the action of the catalyst system, monomer a, monomer b, monomer c and monomer d are mixed for esterification or transesterification reaction, or the esterification or transesterification product of monomer a and monomer b and the esterification or transesterification product of monomer c and monomer d are mixed for copolycondensation reaction.
8. The biodegradable film according to any one of claims 1 to 7, wherein the branched aliphatic-aromatic copolyester has a melt index of 2 to 100 g / 10 min, or 5 to 100 g / 10 min at 190°C under a load of 2.16 kg.
9. The biodegradable film according to any one of claims 1 to 8, wherein the organic peroxide is selected from a dialkyl peroxide, a diacyl peroxide, or a peroxy acid ester.
10. The dialkyl peroxide is selected from dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, or di(tert-butylperoxyisopropyl)benzene; 10. The biodegradable film of claim 9, wherein the diacyl peroxide is selected from benzoyl peroxide or lauroyl peroxide.
11. The biodegradable film according to any one of claims 1 to 10, wherein the organic peroxide is used in an amount of 0.01 to 5 wt %, based on the amount of the branched aliphatic-aromatic copolyester.
12. The biodegradable film according to any one of claims 1 to 11, wherein the copolyester has a melt index of 0.1 to 10 g / 10 min at 190°C under a load of 2.16 kg.
13. 2. The biodegradable film according to claim 1, wherein the amount of the antioxidant is 0.05 to 5 parts, the amount of the slip agent is 0.05 to 5 parts, the amount of the antiblocking agent is 0.05 to 5 parts, and the amount of the nucleating agent is 0.1 to 20 parts, based on 100 parts by weight of the copolyester.
14. 14. The biodegradable film of claim 1 or 13, wherein the antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant in a weight ratio of 1:
1.
15. The hindered phenol antioxidant is selected from Antioxidant 1010, Antioxidant 1076, Antioxidant 245, or Antioxidant 246; 15. The biodegradable film of claim 14, wherein the phosphite antioxidant is selected from triphenyl phosphate, trimethyl phosphate, or antioxidant 168.
16. The slip agent is a stearate or an organic carboxylic acid amide; The antiblocking agent is silica or talc; The biodegradable film of claim 1 or 13, wherein the nucleating agent is selected from hyperbranched polyamide, low density polyethylene, or ethylene-methacrylic acid ionomer.
17. 17. The biodegradable film of claim 16, wherein the stearate is calcium stearate.
18. 17. The biodegradable film of claim 16, wherein the organic carboxylic acid amide is erucamide or oleamide.
19. A method for producing a biodegradable film according to any one of claims 1 to 18, comprising the steps of: Step 1) preparing a copolyester by extrusion reaction of a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d with an organic peroxide; The monomer a is an aromatic dibasic acid or an ester derivative thereof; the monomer b is C 2 -C 10 or an aliphatic dihydric alcohol of C 3 -C 10 and the monomer c is one or more of the alicyclic dihydric alcohols of the formula: 4 -C 20 or an ester derivative thereof; said monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, and an anhydride having a functionality greater than 2; The branched aliphatic-aromatic copolyester is obtained by reacting monomer a, monomer b, monomer c, and monomer d under the action of a catalytic system including at least the second catalyst among a first catalyst, a second catalyst, and a third catalyst; The second catalyst is 3 ) 3 is a compound in which RE is a rare earth metal element, R 3 is a halogen atom, an alkoxy group, an aryloxy group, an acetylacetone group, and R 4 At least one selected from the group consisting of COO- groups, R 4 is C 1 -C 30 is an alkyl group of the formula said first catalyst, when present, is one or more selected from the group consisting of an oxide of M, M(OR 1 ) n and M(OOCR 2 ) m , where M is titanium, antimony or zinc, n and m are each independently a valence of M, R 1 is a C 1 -C 10 alkyl group, and R 2 is a C 1 -C 20 alkyl group; and said third catalyst, when present, being at least one organotin compound; Step 2) extruding and granulating the copolyester obtained in step 1) to obtain a composition; and Step 3) blowing air through the composition to obtain the biodegradable film; Including, In step 2), the copolyester is also mixed with additives, the additives including antioxidants, slip agents, antiblocking agents and nucleating agents. A method for producing a biodegradable film.
20. RE (R 3 ) 3 In the compound of formula (I), RE is lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium, or scandium; The halogen is chlorine or bromine, and the alkoxy group is C 3 -C 6 The aryloxy group is an aryloxy group containing at least one benzene ring and / or naphthalene ring, R 4 is C 1 -C 20 The method of claim 19, wherein the alkyl group is
21. 20. The method of claim 19, wherein the catalyst system further comprises a first catalyst and / or a third catalyst.
22. the total molar ratio of the catalyst to the monomers (a+c) is 1:1000-20000; 22. The method of claim 21, wherein the molar ratio of the first catalyst to the second catalyst to the third catalyst is 0-20:0.1-10:0-1, or 0.1-20:0.1-10:
1.
23. 23. The process according to any one of claims 19 to 22, wherein the amounts of the various monomers are such that the molar ratio of (a+c) to b is 1:0.8-3, the molar ratio of (a+c) to d is 100-2000:1, and the molar ratio of a to c is 0:100-95:5, or 0:100-60:
40.
24. The monomer a is selected from terephthalic acid or dimethyl terephthalate; The monomer b is selected from 1,3-propanediol or 1,4-butanediol; said monomer c is selected from succinic acid, succinic anhydride, dimethyl succinate, adipic acid or dimethyl adipate; The method according to any one of claims 19 to 23, wherein the monomer d is selected from pyromellitic dianhydride, glycerol, pentaerythritol, glycidyl succinate, glycidyl adipate, glycidyl terephthalate, ethylene glycol glycidyl ether, 1,4-butanediol glycidyl ether, glycidic acid, glycidol, 3-hydroxyphthalic anhydride, 4-hydroxyphthalic anhydride, 3-hydroxymethylcaprolactone, and carbonates of 5- or 6-membered rings having an alkylhydroxy group or an alkylcarboxyl group.
25. The branched aliphatic-aromatic copolyester comprises The method according to any one of claims 19 to 24, wherein, under the action of a catalyst system, monomer a, monomer b, monomer c and monomer d are mixed for esterification or transesterification reaction, or the esterification or transesterification product of monomer a and monomer b and the esterification or transesterification product of monomer c and monomer d are prepared to be mixed for copolycondensation reaction.
26. 26. The method of any one of claims 19 to 25, wherein the branched aliphatic-aromatic copolyester has a melt index of 2 to 100 g / 10 min, or 5 to 100 g / 10 min at 190°C under a load of 2.16 kg.
27. 27. The method according to any one of claims 19 to 26, wherein the extrusion temperature in step 1) is from 130 to 190°C, or from 150 to 180°C, or from 160 to 180°C.
28. The method according to any one of claims 19 to 27, wherein the organic peroxide is selected from a dialkyl peroxide, a diacyl peroxide or a peroxy acid ester.
29. The dialkyl peroxide is selected from dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, or di(tert-butylperoxyisopropyl)benzene; 29. The method of claim 28, wherein the diacyl peroxide is selected from benzoyl peroxide or lauroyl peroxide.
30. The method of any one of claims 19 to 29, wherein the organic peroxide is used in an amount of 0.01 to 5 wt %, based on the amount of the branched aliphatic-aromatic copolyester.
31. The method of any one of claims 19 to 30, wherein the copolyester has a melt index of 0.1 to 10 g / 10 min at 190°C under a load of 2.16 kg.
32. 20. The method of claim 19, wherein the amount of the antioxidant is 0.05 to 5 parts, the amount of the slip agent is 0.05 to 5 parts, the amount of the antiblocking agent is 0.05 to 5 parts, and the amount of the nucleating agent is 0.1 to 20 parts, based on 100 parts by weight of the copolyester.
33. 33. The method of claim 19 or 32, wherein the antioxidant is a 1:1 mixture of a hindered phenol antioxidant and a phosphite antioxidant by weight.
34. The hindered phenol antioxidant is selected from Antioxidant 1010, Antioxidant 1076, Antioxidant 245, or Antioxidant 246; 34. The method of claim 33, wherein the phosphite antioxidant is selected from triphenyl phosphate, trimethyl phosphate, or antioxidant 168.
35. The slip agent is a stearate or an organic carboxylic acid amide; The antiblocking agent is silica or talc; 33. The method of claim 19 or 32, wherein the nucleating agent is selected from hyperbranched polyamide, low density polyethylene or ethylene-methacrylic acid ionomer.
36. 36. The method of claim 35, wherein the stearate is calcium stearate.
37. 36. The method of claim 35, wherein the organic carboxylic acid amide is erucamide or oleamide.
38. A copolyester obtained by extrusion reaction of a branched aliphatic-aromatic copolyester derived from monomer a, monomer b, monomer c, and monomer d with an organic peroxide, The monomer a is an aromatic dibasic acid or an ester derivative thereof; The monomer b is C 2 -C 10 or an aliphatic dihydric alcohol of C 3 -C 10 and The monomer c is C 4 -C 20 or an ester derivative thereof; said monomer d is one or more of a polyol having a functionality greater than 2, a polycarboxylic acid having a functionality greater than 2, and an anhydride having a functionality greater than 2; The branched aliphatic-aromatic copolyester is obtained by reacting monomer a, monomer b, monomer c, and monomer d under the action of a catalytic system including at least the second catalyst among a first catalyst, a second catalyst, and a third catalyst; The second catalyst is 3 ) 3 is a compound in which RE is a rare earth metal element, R 3 is a halogen atom, an alkoxy group, an aryloxy group, an acetylacetone group, and R 4 At least one selected from the group consisting of COO- groups, R 4 is C 1 -C 30 is an alkyl group of the formula said first catalyst, when present, is one or more selected from the group consisting of an oxide of M, M(OR 1 ) n and M(OOCR 2 ) m , where M is titanium, antimony or zinc, n and m are each independently a valence of M, R 1 is a C 1 -C 10 alkyl group, and R 2 is a C 1 -C 20 alkyl group; and A copolyester, wherein said third catalyst, when present, is at least one organotin compound.
39. RE (R 3 ) 3 wherein RE is lanthanum, cerium, praseodymium, neodymium, terbium, ytterbium, dysprosium, samarium or scandium; The halogen is chlorine or bromine, and the alkoxy group is C 3 -C 6 The aryloxy group is an aryloxy group containing at least one benzene ring and / or naphthalene ring, R 4 is C 1 -C 20 The copolyester of claim 38, wherein the alkyl group is
40. 40. The copolyester of claim 38, wherein the catalyst system further comprises a first catalyst and / or a third catalyst.
41. the total molar ratio of the catalyst to the monomers (a+c) is 1:1000-20000; 41. The copolyester of claim 40, wherein the molar ratio of the first catalyst to the second catalyst to the third catalyst is 0-20:0.1-10:0-1, or 0.1-20:0.1-10:
1.
42. 42. The copolyester according to any one of claims 38 to 41, wherein the amounts of the various monomers are such that the molar ratio of (a+c) to b is 1:0.8-3, the molar ratio of (a+c) to d is 100-2000:1, and the molar ratio of a to c is 0:100-95:5, or 0:100-60:
40.
43. The monomer a is selected from terephthalic acid or dimethyl terephthalate; The monomer b is selected from ethylene glycol, 1,3-propanediol, or 1,4-butanediol; said monomer c is selected from succinic acid, succinic anhydride, dimethyl succinate, adipic acid or dimethyl adipate; The copolyester according to any one of claims 38 to 42, wherein the monomer d is selected from pyromellitic dianhydride, glycerol, pentaerythritol, glycidyl succinate, glycidyl adipate, glycidyl terephthalate, ethylene glycol glycidyl ether, 1,4-butanediol glycidyl ether, glycidic acid, glycidol, 3-hydroxyphthalic anhydride, 4-hydroxyphthalic anhydride, 3-hydroxymethylcaprolactone, and carbonates having a 5- or 6-membered ring with an alkylhydroxy group or an alkylcarboxyl group.
44. The branched aliphatic-aromatic copolyester comprises The copolyester according to any one of claims 38 to 43, which is prepared such that, under the action of a catalyst system, monomer a, monomer b, monomer c and monomer d are mixed for esterification or transesterification reaction, or the esterification or transesterification product of monomer a and monomer b and the esterification or transesterification product of monomer c and monomer d are mixed for copolycondensation reaction.
45. 45. The copolyester of any one of claims 38 to 44, wherein the branched aliphatic-aromatic copolyester has a melt index of 2 to 100 g / 10 min, or 5 to 100 g / 10 min at 190°C under a load of 2.16 kg.
46. The copolyester of any one of claims 38 to 45, wherein the organic peroxide is selected from a dialkyl peroxide, a diacyl peroxide, or a peroxy acid ester.
47. The dialkyl peroxide is selected from dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, or di(tert-butylperoxyisopropyl)benzene; 47. The copolyester of claim 46, wherein the diacyl peroxide is selected from benzoyl peroxide or lauroyl peroxide.
48. The copolyester of any one of claims 38 to 47, wherein the organic peroxide is used in an amount of 0.01 to 5 weight percent, based on the amount of the branched aliphatic-aromatic copolyester.
49. The copolyester of any one of claims 38 to 48, wherein the copolyester has a melt index of 0.1 to 10 g / 10 min at 190°C under a load of 2.16 kg.
Citation Information
Patent Citations
Biodegradable polyester obtained by reactive extrusion
JP2005523354A
Method for producing polyester resin and hollow molded product made of the polyester resin
JP2006348168A
Aliphatic polyester resin composition, molded article thereof and resin container
JP2009144021A
Biodegradable aliphatic-aromatic polyester
JP2013510213A
Biodegradable Composite, The Preparation Process Thereof, And A Disposable Article Made Therefrom
US20120329924A1